PERFORMANCE IMPROVEMENT TECHNIQUES FOR RSSI BASED LOCALIZATION METHODS - Al Shayokh, Md; Alkasi, Ugur; Partal, Hakan P. (IEEE, 2013)
Performance improvement techniques for two popular RSSI based indoor localization methods have been studied experimentally by using Wi-Fi modems. The improvement of RF Fingerprinting and RSSI Multi-lateration methods have been suggested from different aspects for both line-of-sight (LoS) and non-line-of-sight (nLoS) medium in an indoor environment. Various testing scenarios have been examined for comparison of the two methods, as the performance level in RF Fingerprinting is mainly depend on the number of modems, as well as the density of training data and, the multilateration method is mainly depend on correctly modelling of the path loss exponent. Optimizing and defining a unique path loss exponent for each of the wireless transmitter modems, testing in a LoS and a nLoS medium, changing the number of transmitters, etc, have been tried and performance plots have been shown for comparison purposes.
Keywords: LBS; Indoor localization; RSS(Receive Signal Strength); RF fingerprinting; lateration technique; WiFi based localization; Signal strength to distance conversion; Engineering; Telecommunications